2017
DOI: 10.18632/oncotarget.19773
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor modulates mast cell recruitment in a murine model of prostate cancer

Abstract: Mast cells are important modifiers of prostate tumor microenvironment. The fibroblast growth factor/fibroblast growth factor receptor (FGF/FGFR) system plays a non-redundant autocrine/paracrine role in the growth, vascularization and progression of prostate tumors. Accordingly, the FGF antagonist long pentraxin-3 (PTX3) and the PTX3-derived small molecule FGF-trap NSC12 have been shown to inhibit the growth and vascularization of different FGF-dependent tumor types, including prostate cancer. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Shao et al reported that FGF-FGFR signaling plays an important role in transformation induced by the loss of a PTEN tumor suppressor when combined with the expression of the TMPRSS2/ERG fusion gene [26], and activation of FGF-FGFR signaling by FGF8b overexpression in PTEN deficiency is reported to be associated with prostate tumorigenesis [27]. FGF-FGFR signaling is also related to the induction of an inflammatory response in PCa tissues [28]. The involvement of aberrant FGFR1 signaling in the progression of PCa in particular was demonstrated in several studies.…”
Section: Effects Of the Restoration Of Fgfr2iiib In Prostate Cancementioning
confidence: 99%
“…Shao et al reported that FGF-FGFR signaling plays an important role in transformation induced by the loss of a PTEN tumor suppressor when combined with the expression of the TMPRSS2/ERG fusion gene [26], and activation of FGF-FGFR signaling by FGF8b overexpression in PTEN deficiency is reported to be associated with prostate tumorigenesis [27]. FGF-FGFR signaling is also related to the induction of an inflammatory response in PCa tissues [28]. The involvement of aberrant FGFR1 signaling in the progression of PCa in particular was demonstrated in several studies.…”
Section: Effects Of the Restoration Of Fgfr2iiib In Prostate Cancementioning
confidence: 99%
“…The tissue density of mast cells is highly correlated with the extent of normal and pathologic angiogenesis ( 57 ). Mast cells are recruited by FGF2 ( 58 ) and, in turn, may release FGF2, as well as other pro-angiogenic factors, leading to EC activation ( 59 , 60 ). Accordingly, mast cells and their isolated secretory granules induce an angiogenic response in the chick embryo CAM assay ( 61 ) that is inhibited by neutralizing anti-FGF2 antibodies ( 40 ).…”
Section: Fgf2-dependent Angiogenesis and Inflammationmentioning
confidence: 99%
“…As a consequence of the anti-FGF2/anti-angiogenic activity of PTX3, FGF2-dependent syngeneic tumor grafts of different origin were characterized by impaired FGFR1 activation and reduced CD31 + vascularization and tumor growth when injected in TgN(Tie2-hPTX3) mice ( 106 ). Notably, the TRAMP-C2 prostate adenocarcinoma cell grafts generated in TgN(Tie2-hPTX3) mice were characterized also by a significant decrease of the mast cell infiltrate into the lesion ( 58 ). These data, in keeping with previous observations about the capacity of mast cells to respond chemotactically to FGF2, provide evidence about a relationship among FGF2-dependent mast cell recruitment, angiogenesis, and tumor growth in prostate adenocarcinoma, all hampered by PTX3.…”
Section: Ptx3/fgf Interactionmentioning
confidence: 99%
“…Most members of the pentraxin family can activate the PI3K/AKT/mTOR pathways, thereby interfering with the normal cell- cycle. The neuronal pentraxins and PTX3 possess specific unique receptors that mediates tumor progression ( 15 ). In this review, we have summarized the basic characteristics and functions of each pentraxin family member and highlighted the existing connection between their structures and specific roles in tumor progression.…”
Section: Introductionmentioning
confidence: 99%